Rocky Mountain forests are poised to recover following bark beetle outbreaks but with altered composition. (17th October 2022) - Rodman, Kyle C.; Andrus, Robert A.; Carlson, Amanda R.; Carter, Trevor A.; Chapman, Teresa B.; Coop, Jonathan D.; Fornwalt, Paula J.; Gill, Nathan S.; Harvey, Brian J.; Hoffman, Ashley E.; Kelsey, Katharine C.; Kulakowski, Dominik; et al.
Abstract: Amplified by warming temperatures and drought, recent outbreaks of native bark beetles (Curculionidae: Scolytinae) have caused extensive tree mortality throughout Europe and North America. Despite their ubiquitous nature and important effects on ecosystems, forest recovery following such disturbances is poorly understood, particularly across regions with varying abiotic conditions and outbreak effects. To better understand post‐outbreak recovery across a topographically complex region, we synthesized data from 16 field studies spanning subalpine forests in the Southern Rocky Mountains, USA. From 1997 to 2019, these forests were heavily affected by outbreaks of three native bark beetle species ( Dendroctonus ponderosae, Dendroctonus rufipennis and Dryocoetes confusus ). We compared pre‐ and post‐outbreak forest conditions and developed region‐wide predictive maps of post‐outbreak (1) live basal areas, (2) juvenile densities and (3) height growth rates for the most abundant tree species – aspen ( Populus tremuloides ), Engelmann spruce ( Picea engelmannii ), lodgepole pine ( Pinus contorta ) and subalpine fir ( Abies lasiocarpa ). Beetle‐caused tree mortality reduced the average diameter of live trees by 28.4% (5.6 cm), and species dominance was altered on 27.8% of field plots with shifts away from pine and spruce. However, most plots (82.1%) were likely to recover towards pre‐outbreak tree densities without additional regeneration. Region‐wide maps indicated that fir and aspen, non‐host species for bark beetle species with the most severe effects (i.e. Dendroctonus spp.), will benefit from outbreaks through increased compositional dominance. After accounting for individual size, height growth for all conifer species was more rapid in sites with low winter precipitation, high winter temperatures and severe outbreaks. Synthesis . In subalpine forests of the US Rocky Mountains, recent bark beetle outbreaks have reduced tree size and altered species composition. While eventual recovery of the pre‐outbreak forest structure is likely in most places, changes in species composition may persist for decades. Still, forest communities following bark beetle outbreaks are widely variable due to differences in pre‐outbreak conditions, outbreak severity and abiotic gradients. This regional variability has critical implications for ecosystem services and susceptibility to future disturbances. Abstract : Throughout the US Rocky Mountains, recent bark beetle outbreaks have reduced tree size and altered species composition. While eventual recovery of the pre‐outbreak forest structure is likely in most places, changes in species composition may persist for decades. Post‐outbreak forest communities are widely variable due to differences in pre‐outbreak conditions, outbreak severity, and the abiotic environment.